Smart Territories Competitiveness Based on Data Usage - Del Toro Osorio, Fabiola; Estévez, Elsa; Ospina Becerra, Victoria Eugenia (ACM Digital Library, 2023)
Competitiveness is one of the important goals that economies are trying to achieve. Some experts associate competitiveness with stability and growth, and as such governments are designing solutions to increase competitiveness to improve the quality of life in their communities. To contribute to this goal, we are currently researching how data can be used to increase competitiveness of Smart Territories. This paper presents the progress of our ongoing research that aims to answer the following question: Which artifacts drive the competitiveness of smart territories? This question will help us to answer the overall research question: How to obtain the greatest value from data to contribute to the competitiveness of smart territories?

La competitividad es uno de los objetivos importantes que las economías están tratando de alcanzar. Algunos expertos asocian la competitividad con la estabilidad y el crecimiento y, como tal, los gobiernos están diseñando soluciones para aumentar la competitividad para mejorar la calidad de vida en sus comunidades. Para contribuir a este objetivo, actualmente estamos investigando cómo se pueden utilizar los datos para aumentar la competitividad de los Territorios Inteligentes. Este artículo presenta el progreso de nuestra investigación en curso que apunta a responder la siguiente pregunta: ¿Qué artefactos impulsan la competitividad de los territorios inteligentes? Esta pregunta nos ayudará a dar respuesta a la pregunta general de investigación: ¿Cómo obtener el mayor valor de los datos para contribuir a la competitividad de los territorios inteligentes?
Keywords: Análisis de datos; Data analysis; Desarrollo económico; Economic development; Competencia económica; Competition; Ciudades y territorios inteligentes; Smart cities and territories; Almacenamiento de datos; Data warehousing; Competitiveness; Competitividad; Data; Datos; Smart territory; Territorio inteligente